Nocardiosis and kidney transplantation: case report in a recently transplanted patient - Betônico, Gustavo Navarro (2006)
The patient is a 47-year-old white woman who was on the hemodialysis from 1999 to 2002, when she received a cadaveric renal transplant (deceased donor). The immediate postoperative immunosupression consisted of oral tacrolimus, predinisone and mycofenolato mofetil (MMF), and her medications at that time of her admission were tacrolimus (5mg 12/12 h), MMF (1000mg 12-12 h), and predinisone (10mg/ day). After 8 weeks, the patient went to the hospital and she was admitted presenting fever (37,9ºC), cough, malaise and vomiting. The chest radiography revealed a mass in the left superior lobe, which was initially treated with levofloxacin associated to ceftriaxone. There was partial improvement of the cough and total remission of the fever. The patient was discharged after 3 weeks of treatment in stable condition, with negative blood and bronchial cultures. After ten days, she returned to the hospital with relapsed symptoms and a subcutaneous purulent collection was detected in her left leg, and the culture of the drained material evidenced a filamentous microorganism, identified as Nocardia sp, later specified as Nocardia asteroides. Treatment with sulfametoxazole-trimetroprin 800mg t.i.d was initiated, and after five days, the patient was pyretic and treatment was kept for six months.